Promotion of Pre-natal Education Courses Is Associated With Reducing the Rates of Caesarean Section: A Case-Control Study - Tang, Yunhui; Gao, Jing; Sun, Liping; Gao, Yifei; Guo, Fang; Chen, Qi (Frontiers in Public Health, 2021)
Objective: The number of women having a caesarean section has significantly increased worldwide, in particular in China. Maternal requestion makes a moderate contribution to this increased rate in China. Reducing the caesarean section rate is now becoming a big challenge to midwives and obstetricians as well as health policymakers in China. Our recent survey found that prenatal education course had some positive effects on the reduction of caesarean section on maternal request. However, prenatal education course is relatively new in China. In this study, we investigated whether prenatal education course influences delivery mode in the largest tertiary women’s hospital in China. Methods: In this retrospective study, during the study period, 644 pregnant women attended a prenatal education course and 4,134 pregnant women did not. Data on maternal age, parity, gravida, delivery mode, delivery weeks, birthweight, gestational age at attending prenatal education course and maternal body mass index before pregnancy were collected and analysed. Results: The numbers of women who attempted vaginal delivery were significantly higher in women who attended a prenatal education course, compared to women who did not (87% vs 60%). In addition, the rate of caesarean section on maternal request was 23% in women who attended a prenatal education course. Conclusion: Attendance of a prenatal education course influences the mode of delivery and reduces the unnecessary caesarean section in China. Our findings suggest that the promotion of prenatal education courses is important to reduce the higher caesarean section rate in China, by midwives or obstetricians or health policy-makers as part of China’s strategy.